GREEN HUMAN RESOURCE MANAGEMENT PRACTICES AND SUSTAINABILITY OF MANUFACTURING FIRMS - EKPENYONG, OKON, EMMANUEL; HARRY, EMU, WINIFRED; OBONG, MORGAN, MORGAN; UKAM, EDODI, HOPE (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2025)
As organizations confront increasing environmental pressures, the integration of sustainability into human resource management has emerged as a critical strategic priority. This study investigates the impact of green human resource management (GHRM) practices, specifically green recruitment and selection, green training and development, and green job analysis on the sustainability of manufacturing firms. Guided by the resource-based view theory, the research adopts a survey design and gathers data from 188 employees of Bao Yan Huan Jian Iron & Steel Group in Calabar, Nigeria. Simple linear regression was employed to test the hypothesized relationships. Findings reveal that all three GHRM practices significantly contribute to the sustainability of manufacturing firms. Green recruitment and selection facilitate the hiring of environmentally conscious talent, green training enhances employees’ capabilities to support sustainability goals, and green job analysis aligns job roles with environmental responsibilities. The study concludes that embedding environmental values into HRM systems strengthens organizational resilience and ecological performance. It recommends that firms institutionalize these practices as part of their core sustainability strategies.